An empirical analysis of energy cost pass-through to CO2 emission prices - Hammoudeh, Shawkat (2015)
We use the nonlinear autoregressive distributed lags (NARDL) model to analyse the asymmetric and nonlinear pass-through effects of changes in crude oil prices, natural gas prices, coal prices and electricity prices on the CO2 emission allowance prices. We find that: (i) the crude oil prices have a long-run negative and asymmetric effect on the CO2 allowance prices; (ii) the decreases in the coal prices have a stronger impact on the carbon prices in the short-run than the increases; (iii) the natural gas prices and electricity prices have a symmetric effect on the carbon prices, but this effect is negative for the former and positive for the latter. These findings are robust when using both monthly and daily data and when considering a bivariate and a multivariate models.